Fetty Nur Setiawati PEMBERDAYAAN PEREMPUAN DALAM MEMBANTU MEMENUHI KEBUTUHAN DASAR KELUARGA (STUDI KASUS KELOMPOK WANITA TANI DI PERKEBUNAN KARET WANGUNWATI DESA SUKAWANGUN KECAMATAN KARANGNUNGGAL KABUPATEN TASIKMALAYA) - Nur Setiawati, Fetty (Politeknik Kesejahteraan Sosial Bandung, 2023)
The majority of women in Sukawangun Village, Karangnunggal District, Tasikmalaya Regency rely solely on their husbands' income, resulting in unmet basic family needs. Therefore, the Women Farmers Group in the Wangunwati Rubber Plantation, Sukawangun Village, Karangnunggal District, Tasikmalaya Regency seeks ways to empower women to improve family welfare. The research problems in this study are: 1) How is the empowerment of women through the Women Farmers Group in the Wangunwati Rubber Plantation, Sukawangun Village, Karangnunggal District, Tasikmalaya Regency? 2) How is the fulfillment of basic family needs among women in the Women Farmers Group in the Wangunwati Rubber Plantation, Sukawangun Village, Karangnunggal District, Tasikmalaya Regency? 3) What is the role of members of the Women Farmers Group in helping meet their family's basic needs? The aim of this research is to describe the implementation of women's empowerment in helping meet basic family needs in Sukawangun Village, Karangnunggal District, Tasikmalaya Regency. The research method used is qualitative research. Data collection is done through interviews, qualitative observations, and collecting qualitative documents. Data analysis in this research uses qualitative analysis. The informants in the study are members of the Women Farmers Group who strive to help meet their family's basic needs, as well as the KKPKW management. The results of this study show that: 1) Empowerment is evident from the main objectives or concepts of the formation of this organization, which is to empower women. 2) The fulfillment of basic family needs can be seen from the awareness or understanding of female members regarding the fulfillment of needs due to economic demands, as well as the efforts and achievements made in meeting family needs. 3) The role of members of the Women Farmers Group in helping meet their family's basic needs can be seen from the synergy among members who maintain good relationships. Keywords: Women Farmers Group, Family, Women's Empowerment